2006
DOI: 10.1080/09603100500447537
|View full text |Cite
|
Sign up to set email alerts
|

Does EVA beat earnings and cash flow in Japan?

Abstract: The objective of this paper is to evaluate the effectiveness of Economic Value Added (EVA), a metric that is increasingly used in Japan as a measure of corporate value. EVA is compared with several other valuation measures including cash flow, operating income, and profit after tax from the viewpoint of both levels and changes. Also two different forms of EVA are examined by using the Weighted Cost of Capital (WACC) from the Capital Asset Pricing Model (CAPM) and the WACC from the Fama-French (1993) model. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
2
6
0
4
Order By: Relevance
“…Dotychczas, w literaturze zagranicznej badania poświęcone użyteczności zysku ekonomicznego w wyjaśnianiu zmian miar rynkowych przedsiębiorstw, przy założeniu różnych metod estymacji kosztu kapitału własnego, były prowadzone m.in. dla danych z rynku tureckiego (Erdogan i in., 2000) i japońskiego (Tsuji, 2006). …”
Section: Koszt Kapitału Własnego Jako Komponent Zysku Ekonomicznegounclassified
“…Dotychczas, w literaturze zagranicznej badania poświęcone użyteczności zysku ekonomicznego w wyjaśnianiu zmian miar rynkowych przedsiębiorstw, przy założeniu różnych metod estymacji kosztu kapitału własnego, były prowadzone m.in. dla danych z rynku tureckiego (Erdogan i in., 2000) i japońskiego (Tsuji, 2006). …”
Section: Koszt Kapitału Własnego Jako Komponent Zysku Ekonomicznegounclassified
“…Para responder, é necessário calcular o valor das empresas. A sugestão, no presente caso de ensino, é fazê-lo por lucro econômico (valor da empresa ou firm value é a soma do capital investido (neste caso, o ativo operacional total) com o valor presente da agregação de valor, ou seja, o valor presente dos lucros econômicos (Miller e Modigliani, 1961;O'Byrne, 1996;Tsuji, 2006e Assaf Neto, 2014 Outras possibilidades a serem exploradassugestão 2:…”
Section: Qual Empresa é a Melhor Candidataparteunclassified
“…This means that if managements' future earnings expectations affect their current dividend payouts decisions, then dividend changes will convey information to the market regarding future earnings. Allen and Michaely (2003) as cited in Tsuji (2012) also documented that the dividend-information/signaling hypotheses included three important implications that had been empirically examined:…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Citing Miller and Modigliani (1961), Tsuji (2012) suggested that the information content of dividend policy should apply. This means that if managements' future earnings expectations affect their current dividend payouts decisions, then dividend changes will convey information to the market regarding future earnings.…”
Section: Theoretical Frameworkmentioning
confidence: 99%